Research on fatigue vulnerable details of cross beam joints after reinforcement for steel truss bridges - Tan Jinhua; Jiang Youwei; Li Yueguang; Liu Yang (Informes de la Construccion, 2023)
In this research, fatigue tests on full-size specimens are conducted for a steel cross-beam joint before and after reinforcement. Combined with a three-dimensional (3D) numerical simulation, the 3D stress parameters, and their redistribution rules study anew with a web crack and new crack initiation locations and fatigue weakness details are predicted. The research results include the following: 1) The empirical formula parameter m of the Z-axis stress for the new crack tip is approximately 0.05. 2) The fatigue performance of the web’s new crack tips is significantly improved by bolting reinforced steel plates, the stress range is reduced by 60%-98.78%, and the original crack stops growing in size. The health monitoring system can choose the predicted weak details as valid monitoring points so that the fatigue damage can be intelligently perceived after the reinforcement of steel bridges.